Fatimid Library: History, Development and Management - Akmam, Nakhlu Zatul; Shamsuzzoha, ATM (Journal of the Bangladesh Association of Young Researchers, 2014)
In demand of time Muslim library has been initiated from the very beginning of Islam like the ancient Mesopotamian, Egyptian and Roman libraries. With the arrival of Prophet Muhammad (Sm.) a new epoch was started in the field of knowledge and science in Islam. From that very day with the appearance of Prophet (Sm.) the beginning of Islamic civilization get impetus and many institutions were established in the Muslim countries and renowned intellectuals and scholars of different fields were associated with those institutions. After this, when the Muslims came closer to the Persian literature and Greek sciences the Islamic library started its journey in the 7th century. So, for the acquisition of knowledge Muslim library has been initiated at Baghdad and later on Muslim Spain and Africa. In this process, as a strong opponent of the Abbasids the Fatimid rulers made tremendous steps in the field of establishing library and library management. As a strong opponent of the Abbasid the Fatimid established royal library and various public libraries. Various important functions such as, collection of books, preservation system, translation, cataloguing, inclusion and clarification of the books were practices in those libraries. Besides these, recruitment, promotion, management of archives and modern system of budgeting were also salient features of their library management. The current research is a humble attempt to find out the functioning, evolution and analyzing of the Fatimid royal, private and public libraries. DOI: http://dx.doi.org/10.3329/jbayr.v2i1.20538 Journal of the Bangladesh Association of Young Researchers (JBAYR): Vol.2(1), 2012 & 2013: 21-32